GEOS-Chem Code v11-01 - Sam Silva (Zenodo, 2020)
This is the GEOS-Chem Code used in Silva et al. (Submitted),"Exploring the Constraints on Simulated Aerosol Sources and Transport across the North Atlantic with Island-Based Sun Photometers"